Law School Success: A Matter of Heart - Campagnolo, Yan (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
On September 3, 2024, at the start of the academic year, Vice-Dean Yan Campagnolo addressed the new students of the University of Ottawa Faculty of Law. His speech outlined the key qualities that the most successful students exhibit: they are consistent, organized, efficient, ultra-hardworking, and rigorous. Together, the first letters of each of these qualities make the acronym “C.O.E.U.R.”, the French word for “heart”. The speech shows that success at law school is thus ultimately an affaire de cœur—a matter of heart.